Study of Color Classification and Its Psychological Effects - Sadat, Sayed Rasuol (Journal of Social Sciences - Kabul University, 2020)
Human beings possess the ability to distinguish and categorize colors through vision. However, an essential question arises: how do people perceive and recognize colors, and how are color names assigned? Significant research has been conducted in this field. In human society, colors are generally classified into primary categories, including white, black, red, green, yellow, orange, blue, and purple. The results of this study relate to the classification of colors, their functions, and the psychological impact of color perception, as observed through experiments and production outcomes.